A new CERAD total score with equally weighted z-scores and additional executive and non-amnestic „CERAD-Plus" tests enhances cognitive diagnosis in patients with Parkinson's disease: Evidence from the LANDSCAPE study. (September 2021) - Lillig, Robert; Ophey, Anja; Schulz, Jörg B.; Reetz, Kathrin; Wojtala, Jennifer; Storch, Alexander; Liepelt-Scarfone, Inga; Becker, Sara; Berg, Daniela; Balzer-Geldsetzer, Monika; Kassubek, Jan; Hilker-Roggendorf, Rüdiger; et al.
Abstract: Introduction: The Consortium to Establish a Registry for Alzheimer's Disease (CERAD) is a renowned cognitive test battery, which has been extended in its German version to the CERAD-Plus including tests of executive functions and processing speed. The most commonly used total score (TS) is based on the restricted CERAD version and reflects the sum of selected raw-values (Chandler et al., 2005). The CERAD-Plus extensions might be of particular diagnostic utility for cognitive assessments in Parkinson's Disease (PD), as executive functions and processing speed belong to the most vulnerable domains in PD. Objective: The aim was to develop a CERAD-TS based on the extended CERAD-Plus' age-, gender-, and education-corrected z-scores and to evaluate its diagnostic accuracy compared to the established CERAD-Chandler-TS. Methods: Baseline data of n  = 679 patients with PD (69% male, n  = 277 PD without cognitive impairment, n  = 307 PD-MCI, n  = 95 PD-D) from the multicenter, prospective DEMPARK/LANDSCAPE study were analyzed. ROC-analyses were conducted for four different TS that were either based on the original CERAD or CERAD-Plus, on raw-values or z -scores, and equally-weighted or based on factor scores. AUC-comparisons were conducted to determine the best yet most parsimonious TS. Results: The newly designed CERAD-Plus-TS based on equally-weighted z -scores outperformed both the CERAD-Chandler-TS and cognitive screening instruments when differentiating between individuals with PD of varying cognitive impairment (0.78 ≤ AUC ≤ 0.98). Conclusion: Results suggest a high relevance of non-amnestic subscales for the cognitive assessment in PD populations. The proposed CERAD-Plus-TS needs further validation. The extensions might offer diagnostic potential for non-PD populations as well. Highlights: A new, extended CERAD total score (TS) using equally weighted standardized z-scores was developed. The TS proved best and most parsimonious for diagnosing cognitive dysfunction in Parkinson's Disease (PD). Executive and further non-amnestic tests improved diagnostic accuracy in PD. PD patients ( n  = 679) with varying cognitive impairment were included in ROC analyses. The TS needs further validation and might be of value in populations other than PD.